Impact of capital structure on investor behavior and performance of firms in Pakistan / Aamir Farooq, Abdul Jabbar Ahsan, Kush Bakhat Umer, Asma Irum, and Madiha Latif - Umer, Kush Bakhat; Irum, Asma (Faculty of Business Management, 2013)
The purpose of this article is to find out that capital structure which has a positive impact on the investor behaviour and firm‟s performance. This article explains the impact of capital structure on investor behaviour and performance of firms in Pakistan. Study on capital structure proves that an organization Capital structure plays a vital role in determining financial performance, sustainability and future growth of the organization. In this paper impact of capital structure has been shown through a conceptual framework. This study provides guidelines for developing countries that capital structure increases performance of firms and create a positivity in investor behaviour. It is also seen that different choices of capital structure influences behaviour of investors. In other words investor behaviour has been changed due to changes in pattern of capital structure. That‟s why investors should have the correct knowledge regarding combination of debt and equity of a firm. This research is useful for Pakistani firms and by using these guidelines firms can develop a good capital structure.